2021
DOI: 10.31940/jbk.v17i2.2357
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Organizational Climate on Knowledge-Sharing Behavior: An Empirical Study in Minimarkets

Abstract: This empirical research aims to identify the relationship between organizational climate and knowledge sharing behavior. Also, this study uses knowledge sharing intentions as a mediator between these two variables. The survey was conducted incidentally on 403 minimarket employees in eight districts/cities in West Java. Factor analysis was employed to purify research variables. To evaluate the research model, multiple regression analysis was used. The results of the factor analysis on organizational climate res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
0
0
Order By: Relevance
“…An organizational climate that does not support employee growth and development can also contribute to high turnover rates. This is in line with research conducted by Raharso (2021) which found that lack of opportunities for career development was one of the reasons for employee turnover. When employees feel they do not have opportunities to learn and develop within the company, they may seek better career opportunities elsewhere that offer better development opportunities.…”
Section: Introductionsupporting
confidence: 91%
“…An organizational climate that does not support employee growth and development can also contribute to high turnover rates. This is in line with research conducted by Raharso (2021) which found that lack of opportunities for career development was one of the reasons for employee turnover. When employees feel they do not have opportunities to learn and develop within the company, they may seek better career opportunities elsewhere that offer better development opportunities.…”
Section: Introductionsupporting
confidence: 91%
“…Knowledge is the key enterprise input for transforming innovative ideas into outcomes. It is used to develop new products and improve business organizational and marketing methods and techniques [20][21][22]. The knowledge flow increases the enterprise's performance [23], assists in achieving innovation activities efficiently [24], and enhances the enterprise's absorption capacity [25].…”
Section: Introductionmentioning
confidence: 99%